2011
DOI: 10.1097/igc.0b013e31821c45b7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Macrophage Migration Inhibitory Factor and CD74 in Cervical Squamous Cell Carcinoma

Abstract: Overexpression of MIF and CD74 in SCC and its precancerous lesions and the up-regulation of VEGF secretion in cervical cancer cells indicate that MIF and CD74 may play critical roles in the pathogenesis and angiogenesis of cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 18 publications
2
35
1
Order By: Relevance
“…ISO-1[(S, R)-3-(4-hydroxyphenyl)-4, 5-dihydro-5-isoxazole acetic acid methyl ester)], a prototype inhibitor of MIF (Al-Abed & VanPatten, 2011), reduced the tumor size and angiogenesis in the mouse xenograft model of DU-145 prostate cancer (Meyer-Siegler et al, 2006). MIF and CD74, through their over-expression, are known to enhance VEGF's expression in cervical cancer (Cheng et al, 2011). In neuroblastoma, N-myc expression is linked with advanced stage (Ren et al, 2004).…”
Section: Mif and Angiogenesismentioning
confidence: 99%
“…ISO-1[(S, R)-3-(4-hydroxyphenyl)-4, 5-dihydro-5-isoxazole acetic acid methyl ester)], a prototype inhibitor of MIF (Al-Abed & VanPatten, 2011), reduced the tumor size and angiogenesis in the mouse xenograft model of DU-145 prostate cancer (Meyer-Siegler et al, 2006). MIF and CD74, through their over-expression, are known to enhance VEGF's expression in cervical cancer (Cheng et al, 2011). In neuroblastoma, N-myc expression is linked with advanced stage (Ren et al, 2004).…”
Section: Mif and Angiogenesismentioning
confidence: 99%
“…As an important proinflammatory cytokine, MIF can counteract glucocorticoid signaling by activating immune or inflammatory cells and promoting inflammatory cytokine release [9]. Moreover, MIF has been shown to induce various pathologic events, such as acute respiratory distress syndrome [15], arthritis [22], glomerulonephritis [20], and angiogenesis [12,30]. Moreover, Type 1 Modic changes of cartilage end plates are characterized by an inflammatory reaction, but to our knowledge, the relationship between MIF and cartilage end plates with Type 1 Modic changes has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study showed that MIF induced VEGF secretion in a dose-dependent manner in cervical cancer cells, which could be inhibited by anti-CD74 antibody (Cheng et al 2011a). To study the effects on VEGF secretion in thyroid cancer, BCPAP and K1 cells were treated with the same experimental protocol previously used.…”
Section: Decreased Vegf Secretion With Anti-cd74 Antibody Treatmentmentioning
confidence: 99%
“…This ligand-receptor interaction may be an important link between chronic inflammation and carcinogenesis (Bucala & Donnelly 2007). The expression of MIF and/or CD74 has been explored in several forms of cancer (Ren et al 2005, Xu et al 2008, Nagata et al 2009, Cheng et al 2011a). In addition, MIF has been identified as a hypoxia-induced gene, and its expression serves to activate a proangiogenic transcriptional program (Winner et al 2007).…”
Section: Introductionmentioning
confidence: 99%